Analysis of Islamic Business Ethics on the Production Process of Dumma Official Muslim Fashion: An Ethnometodological Approach - Furqon Ariawansyah; R. Melda Maesarach (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the application of Islamic business ethics in the production process at DUMMA Official and its impact on operational efficiency, work culture, and customer loyalty. The research problem stems from the lack of empirical studies that discuss how sharia principles are not only normative but also contribute to effective and sustainable business practices. To fill this research gap, the study was conducted using a qualitative approach through in-depth interviews, observation, and analysis of company documents. The results show that the implementation of values such as honesty, justice, social responsibility, and transparency contributes positively to the company's performance. Shariah-based SOPs and flexibility in working hours for religious needs enhance operational efficiency, while transparency in reporting and the use of halal and thayyib raw materials foster customer loyalty. This study offers implications for similar companies to adopt Islamic business ethics principles, thereby creating a balance between operational success and spiritual benefits.